2022
DOI: 10.17269/s41997-022-00643-7
|View full text |Cite
|
Sign up to set email alerts
|

The working conditions for personal support workers in the Greater Toronto Area during the COVID-19 pandemic: a mixed-methods study

Abstract: Objective During the height of the COVID-19 pandemic, personal support workers (PSWs) were heralded as healthcare ‘heroes’ as many of them cared for high-risk, vulnerable older populations, and worked in long-term care, which experienced a high number of COVID-19 outbreaks and deaths. While essential to the healthcare workforce, there is little understanding of PSW working conditions during the pandemic. The aim of our study was to examine the working conditions (including job security, work polic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 23 publications
2
22
1
1
Order By: Relevance
“…34 For PSWs in our study, the COVID-19 pandemic exacerbated many of these preexisting arrays of cooccurring, job-related factors including low wages, transportation, work-stress, scheduling inconsistencies, and the realities of isolated work. Our findings are aligned with those reported by authors Hapsari et al, 35 who examined the experiences of PSWs working in home and long-term care facilities during the COVID-19 pandemic, and found overlapping experiences around working conditions, job security, and well-being. Our study complements their findings through the understanding of intrinsic rewards as motivating factors, which explain the interconnected relationships between clients and PSWs' occupational conditions in the context of the pandemic.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…34 For PSWs in our study, the COVID-19 pandemic exacerbated many of these preexisting arrays of cooccurring, job-related factors including low wages, transportation, work-stress, scheduling inconsistencies, and the realities of isolated work. Our findings are aligned with those reported by authors Hapsari et al, 35 who examined the experiences of PSWs working in home and long-term care facilities during the COVID-19 pandemic, and found overlapping experiences around working conditions, job security, and well-being. Our study complements their findings through the understanding of intrinsic rewards as motivating factors, which explain the interconnected relationships between clients and PSWs' occupational conditions in the context of the pandemic.…”
Section: Discussionsupporting
confidence: 92%
“…Our study complements their findings through the understanding of intrinsic rewards as motivating factors, which explain the interconnected relationships between clients and PSWs' occupational conditions in the context of the pandemic. Similar accounts of stress and "pandemic anxiety" described by participants suggest to us increased emotional labor and risk for burnout; unlike the accounts of support described by Hapsari et al, 35 support systems were not well defined for PSWs in our study. Organizational support can, however, act as mediating factors against the increased occupational stress of working as a PSW during a global pandemic (eg, up-to-date information and access to PPE).…”
Section: Discussioncontrasting
confidence: 64%
“…These demographic characteristics are also presented elsewhere. 33 Overall, 86.5% (95% CI 80.7%-92.4%) of the participants were precariously employed (Figure 1). For example, 49.3% (95% CI 40.9%-57.8%) mainly worked part-time hours and 65.3% (95% CI 57.4%-73.1%) were in nonpermanent contract positions (Table 2).…”
Section: Resultsmentioning
confidence: 98%
“…Two other papers focused specifically on the social inequity impacts of government emergency measures and new economic policies at the micro level. Hapsari and colleagues (Hapsari et al, 2022) found personal support workers' (PSW) pre-existing poor work conditions of job insecurity and lack of paid sick leave and other benefits exacerbated COVID-19-related challenges. During the height of the COVID-19 pandemic, PSWs were subjected to increased stress and poorer overall mental health and were largely left to fend for themselves with these additional burdens.…”
Section: Overview Of Included Papersmentioning
confidence: 99%
“…Deux autres communications portent spécifiquement sur l'effet sur les iniquités sociales des mesures d'urgence imposées par les gouvernements et des nouvelles politiques économiques à l'échelle micro. Hapsari et collègues (Hapsari et al, 2022) ont constaté que les mauvaises conditions de travail préexistantes des préposés aux bénéficiaires (PAB)l'insécurité d'emploi et l'absence de congés de maladie payés et d'autres avantagesont exacerbé les difficultés causées par la COVID-19. Au plus fort de la pandémie, les PAB ont subi un stress accru, leur santé mentale générale a dépéri, et on les a laissés dans une large mesure se débrouiller seuls avec ces fardeaux supplémentaires.…”
Section: Aperçu Des Communications Acceptéesunclassified